Bulk density density and its implications on dynamic bending of Hovenia dulcis Thunb Wood - Talgatti, Maiara; Susin, Felipe; Carvalho, Douglas Edson; Santini, Elio José (Scientia Agraria Paranaensis, 2017)
O estudo teve por objetivo avaliar a influência da massa específica no ensaio This study aimed to verify the basic density influence in dynamic bending trails of Hovenia dulcis Thunb wood. In order to do so, 34 samples of heart wood were used, with the following dimensions: 30 x 2 x 2 cm (longitudinal, radial and tangential) respectively, according to the Brazilian standard, NBR 7190 (1997). The samples were evaluated for their bulk density for the rate between the weight in 12% of moisture and its respective volume, and posteriorly, it was separated in two groups: the first with specific weight between 0.55 and 0.64 g cm-3 and the second one between 0.65 and 0.75 g cm-3, aiming the comparison between the treatments. The wood resistance for the dynamic bending was estimated, using the Charpy’s impact test, in the radial direction. Posteriorly, the samples were evaluated according to their break pattern and according to the specimen moisture rate. It was analyzed the relation between the apparent specific weight and the dynamic bending, adjusting a linear model that relates this two variables, obtaining an adjusted coefficient of determination of 0.81. It was observed difference between the absorbed work, resilience coefficient and the dynamic dimension due to the specific weight of the material.